FREQUENCY OF ADVERSE PERINATAL OUTCOME IN WOMEN WITH POLYHYDRAMNIOS ADMITTED AT TERTIARY CARE HOSPITAL - Kiran Wassan; Sumera Sheikh (Journal of University Medical & Dental College, 2018)
ABSTRACT: Polyhydramnios refers to the excessive accumulation of liquor amnii more than 2 liter, which is likely to inﬂuence the course of pregnancy and labour. The maintenance of amniotic ﬂuid volume within normal limits is an important indicator of fetal well-being, so when polyhydramnios is detected during pregnancy, it should be investigated thoroughly because of its association with several maternal and fetal complications. Although, 60% of cases are idiopathic. The most common causes are fetal anomalies maternal diabetes and twin pregnancy. The aim of the study is to ﬁnd out the frequency of an adverse perinatal outcome. The adverse perinatal outcome was determined by the presence of congenital anomalies and other neonatal adverse parameters which are solely caused by polyhydramnios. OBJECTIVE: To determine the frequency of an adverse perinatal outcome in women with Polyhydramnios. STUDY DESIGN: Descriptive-Cross sectional. SETTING: The study was conducted at the Department of Gynecology and Obstetrics, Unit-I Liaquat University of Medical and Health Sciences, Hyderabad / Jamshoro (LUMHS). DURATION OF STUDY: This study was carried out for the period of 6 months, i.e. from 25th Dec 2009 to 25th June 2010. RESULTS: Study outcome was measured by immediate neonatal assessment after birth. Out of 79 patients, 19(24.05%) women delivered with congenitally malformed babies. Among that CNS system involvement was more frequent, i.e. anencephalus 6(7.59%) and Hydrocephalus 8(10.13%). GIT anomalies were 5(6.33%). 13(16.46%) babies were born with low Apgar score, 4(5.06%) had low birth weight and most of the babies were preterm i.e. 50 (63.29%). The categorical data is presented via diﬀerent tables and pie charts and the possible confounding variable i.e. age, gestational age, and parity, that could aﬀect the outcome were analyzed. CONCLUSION: It is concluded that polyhydramnios carries a higher incidence of adverse perinatal outcomes like congenital anomalies, low birth weight, low Apgar score and preterm gestation. It is imperative to make eﬀorts to antenatally detect as many cases as possible to provide proper perinatal care. So these women should have early antenatal booking visits and should be fully investigated for the cause of polyhydramnios and need to be encouraged to take folic acid supplementation.